Gender, age cohort, and household investment in child schooling: New evidence from sub-Saharan Africa - Abdul Malik Iddrisu; Michael Danquah; Alfred Barimah; Williams Ohemeng (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Sub-Saharan Africa continues to post one of the highest gender gaps in educational outcomes in the world. Gender gaps in educational outcomes might be attributed to an uneven allocation of household resources towards the schooling of boys and girls. In this paper, we interrogate this issue using individual-level data from Ghana. Methodologically, the paper explores two potential sources of gender bias: bias in the decision to enrol/keep boys and girls in school; and bias in the educational expenditure on boys and girls enrolled in school. Our findings are illuminating: gender bias in households' educational expenditure allocations arises mainly from the decision to enrol or not boys and girls in school, where an important pro-male bias exists. That is, households favour boys in their decision whether or not to enrol a child in school in Ghana. However, after enrolment, households tend to spend an equal amount on the schooling of both boys and girls. These findings have important implications for educational policy design, especially in the context of developing countries.
Keywords: D13; I21; I22; 330; educational expenditures; gender bias; household; human capital